1993
DOI: 10.1093/oxfordjournals.jbchem.a124274
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Lysosomal Sialidase1

Abstract: An acid sialidase [EC 3.2.1.18], partially purified from human placenta by Con A-Sepharose adsorption and p-aminophenyl thio-beta-D-galactoside-CH-Sepharose (PATG-Sepharose) affinity chromatographies, was activated by incubation at 37 degrees C. This activation showed both time and temperature dependencies, with the most effective activation observed at 37 degrees C in the pH range between 4.3 and 5.2. The influence of various protease inhibitors on its activation was investigated. Among the protease inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In contrast other researchers hypothesized that activation of sialidase in itro involves its proteolytic processing [39,40]. To understand the molecular mechanism associated with the activation process we performed the Western blotting of sialidase in the samples obtained in the process of the 120 min incubation of the concentrated glycoprotein fraction at 37 mC (Figure 2c), which increased the specific activity of sialidase from 0n94 mU\mg to 3n5 mU\mg (Figure 2d).…”
Section: Figure 4 Electron Micrograph Of Normal Fibroblasts Transfectmentioning
confidence: 90%
“…In contrast other researchers hypothesized that activation of sialidase in itro involves its proteolytic processing [39,40]. To understand the molecular mechanism associated with the activation process we performed the Western blotting of sialidase in the samples obtained in the process of the 120 min incubation of the concentrated glycoprotein fraction at 37 mC (Figure 2c), which increased the specific activity of sialidase from 0n94 mU\mg to 3n5 mU\mg (Figure 2d).…”
Section: Figure 4 Electron Micrograph Of Normal Fibroblasts Transfectmentioning
confidence: 90%
“…The activation occurs in a time-and pH-dependent fashion, suggesting involvement of certain enzymatic modification(s) in the activation process. Activation of neuraminidase did not occur in a liver sample of a patient with galactosialidosis [96], raising a possibility that the deficiency of the cathepsin A activity might have influenced the activation process. A recent study demonstrated that neuraminidase bound to cathepsin A precursor, shortly after its synthesis, was transported to lysosomes.…”
Section: Galactosialidosis and Activation Of Human Lysosomal Neuraminmentioning
confidence: 93%
“…Human lysosomal neuraminidase in a partially purified preparation is activated by brief incubation under acidic pH condition [84,[93][94][95][96]. The activation occurs in a time-and pH-dependent fashion, suggesting involvement of certain enzymatic modification(s) in the activation process.…”
Section: Galactosialidosis and Activation Of Human Lysosomal Neuraminmentioning
confidence: 99%
“…5B), we do not know whether these trace level contaminants contribute to the distinctive pattern of endothelial barrier disruption. We did not use protease inhibitors in our preparations because of the concern that protease inhibitors can affect neuraminidase activity, as was previously described by Hiraiwa and colleagues (9). However, to rule out influence of other factors in this preparation, we heat-inactivated the enzyme as described above for the neuraminidase from Clostridium perfringens.…”
Section: Sialic Acids Contribute To the Glycocalyx Of Paecs Andmentioning
confidence: 99%